Algeria : 2011 Article IV Consultation: Staff Report; Public Information Notice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2011 Article IV Consultation reports that despite an uncertain international economic environment, the Algerian economy has been doing relatively well. Real nonhydrocarbon GDP growth in 2010 reached 6 percent and total GDP growth was 3 percent. Executive Directors have welcomed Algeria's overall good economic performance in recent years amid a difficult international economic environment. Nevertheless, they noted that significant challenges persist, and have encouraged the authorities to renew their efforts to preserve macroeconomic stability, restore fiscal prudence, and diversify the economy with a stronger private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet